Responding to Evolving Megatrends - CGIAR Independent Science for Development Council (2023)
Since the launch of CGIAR’s 2030 Research and Innovation Strategy (CGIAR Strategy) in 2021, the trajectory, frequency, and pace of known trends and cycles have changed, and the world has experienced an increasing array and severity of global shocks. As CGIAR prepares its 2025–2027 research and innovation portfolio, this is an appropriate time to examine the effects of these changes. Accordingly, the Independent Science for Development Council (ISDC) commissioned a 2023 project to answer the following questions: